PENDAMPINGAN GURU DALAM PENGEMBANGAN NILAI MODERASI BERAGAMA MELALUI BUDAYA KELAS DI SMP NEGERI TENGGARONG SEBERANG - Nasiah, Siti; Hajriana, Hajriana (LPPM Universitas Islam 45 Bekasi, 2025)
Tenggarong Seberang Sub-district is an area with a diverse population in terms of religion, ethnicity, language, traditions and so on, so that schools as miniature communities also have diverse students. This causes the need for the cultivation of religious moderation values in schools. However, most of the PAI teachers at SMPN in the Tenggarong Seberang sub-district have not been able to fully integrate the values of religious moderation, especially in shaping classroom culture. The purpose of the service was to assist PAI teachers at SMPN Tenggarong Seberang in developing the value of religious moderation through classroom culture. This dedication uses the Participation Action Research (PAR) method. The results showed that the mentoring activities to PAI teachers in developing the value of religious moderation through classroom culture were successful in assisting in designing lesson plans that integrated the value of religious moderation and assisting the implementation of learning which showed that PAI teachers were able to develop the value of religious moderation in the aspect of classroom management, namely roling seating, students leading prayers alternately every meeting, reading religious moderation quotes; in the aspect of teaching methods and materials, namely questioning activities, material with themes that contain religious moderation values, and dialogical methods; and aspects of the classroom atmosphere in the form of writing religious moderation quotes, planning to decorate religious moderation quotes, making student profiles, procuring finding cabinets, and developing literacy corners with books that strengthen the cultivation of religious moderation values (for those that already exist) and procuring literacy corners for those that do not exist.